The fate of inhaled uranium-containing particles upon clearance to gastrointestinal tract. Issue 8 (2nd August 2022) - Hettiarachchi, Eshani; Das, Milton; Cadol, Daniel; Frey, Bonnie A.; Rubasinghege, Gayan
Abstract : Uranium mine dust that enters the gastrointestinal (GI) tract can dissolve to yield uranyl cation, U(vi ). The type of uranium mineral and the overall mineral composition of the dust plays a vital role in the extent of toxicity. Abstract : Uranium-bearing respirable dust can cause various health problems, such as cardiovascular and neurological disorders, cancers, immunosuppression, and autoimmunity. Exposure to elevated levels of uranium is linked to many such health conditions in Navajo Nation residents in northwestern New Mexico. Most studies have focused on the fate of inhaled dust particles (<4 μm) in the lungs. However, larger-sized inhaled particles (10–20 μm) can be cleared to the human gastrointestinal tract (GIT), thereby enabling them to interact with stomach and intestinal fluids. Despite the vital importance of understanding the fate of uranium-bearing solids entering the human GIT and their impact on body tissues, cells, and gut microbiota, our understanding remains limited. This study investigated uranium solubility from dust and sediment samples collected near two uranium mines in the Grants Mining District in New Mexico in two simulated gastrointestinal fluids representing fasting conditions in the GIT: Simulated Gastric Fluid (SGF) and Simulated Intestinal Fluid (SIF). The dissolution of uranium from dust depends on its mineralogy, fluid pH, and composition. The dust samples from the Jackpile mine favored higher solubility in the SIF solution, whereas the sediment samples from the St. Anthony Mine favored higher solubility in the SGF solution. Further, geochemical calculations performed with the PHREEQC modeling program suggested that samples rich in the minerals andersonite, tyuyamunite, and/or autunite have higher uranium dissolution in the SIF solution than in the SGF solution. We also tested the effect of added kaolinite and microcline, which are both present in some samples. The ratio of dissolved uranium in SGF relative to SIF decreases with the addition of kaolinite for all mineral phases but andersonite. With the addition of microcline, the ratio of dissolved uranium in SGF relative to SIF decreases for all the tested uranium minerals. The most prevalent oxidation state of dissolved uranium was computationally determined as +6, U(vi ). The geochemical calculations made with PHREEQC agree with the experimentally observed results. Therefore, this study gives insight into the mineralogy-controlled toxicological assessment of uranium-containing inhaled dust cleared to the gastrointestinal tract.